DEVELOPMENT OF JUWANA HERITAGE IN MATHEMATICS ANDROID APPLICATION INTEGRATED WITH PROBLEM-BASED LEARNING ASSISTED BY ADOBE ANIMATION TO IMPROVE MATHEMATICAL PROBLEM SOLVING SKILLS - Detalia Noriza Munahefi; Alifia Sabila Al-qonita (IAIN Ambon, 2025)
Mathematical problem-solving skills need to be developed to achieve the SDGs, specifically in quality education. However, the results of the 2022 PISA (Philosophy of Mathematics) show that the problem-solving ability of students in Indonesia is relatively low. Innovation is needed to improve problem-solving abilities by developing an Android application integrated with Problem-Based Learning (PBL) with cultural nuances. The study aims to develop an Android application,